Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam Dengan Alat Peraga Nyata Pada Siswa Kelas VI - Asep Sutisna Sanjaya (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to improve the learning outcomes of sixth-grade students in Natural Sciences (IPA) subject through the application of concrete teaching aids in the learning process. The method used is Classroom Action Research (CAR) with two cycles. The research subjects are 27 sixth-grade students in SDN Pisangan Baru 01, East Jakarta, in the academic year 2018/2019. The results show that the use of concrete teaching aids effectively enhances students' learning outcomes, as evidenced by the increase in the average score from 57.77 in the initial test to 73.7 in the second cycle. Data analysis was conducted through observation and evaluation of students' learning outcomes. These findings indicate that concrete teaching aids can stimulate students' interest in learning, increase active participation, and facilitate understanding of IPA concepts. These results have positive implications for teaching practices in schools by emphasizing the importance of using methods that are suitable for students' characteristics to achieve the desired learning objectives. Thus, this research contributes to the understanding and development of effective teaching methods in the context of elementary education.